Solution-focused brief therapy in schools : a 360-degree view of research and practice - Kelly, Michael S. (Michael Stokely), 1968-; Kim, Johnny S.; Franklin, Cynthia (Oxford : Oxford University Press, 2008)
Since its creation in the 1980s, solution-focused brief therapy (SFBT) has gradually become a common and accepted treatment option for many mental health professionals. This book gives school social workers the tools they need to understand and use SFBT with students, families, teachers, and administrators.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Educational counseling -- United States; Solution-focused brief therapy -- United States; School social work -- United States